Downregulation of Long Non-coding RNA Nuclear Paraspeckle Assembly Transcript 1 Inhibits MEG-01 Differentiation and Platelet-Like Particles Activity - Bian, Weihua; Chen, Wangping; Jiang, Xiaoli; Qu, Huiqing; Jiang, Jing; Yang, Jinfu; Liang, Xinyue; Zhao, Bingrui; Sun, Yeying; Zhang, Chunxiang (Frontiers in Genetics, 2020)
Platelets are derived from megakaryocytes and play an important role in blood coagulation. By using high throughput sequencing, we have found that the long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NEAT1) is abundant in platelets (GEO ID: 200097348). However, little is known about its role in regulating megakaryocyte differentiation and platelet activity. This study aims to clarify the effect of NEAT1 on MEG-01 differentiation and platelet-like particle (PLP) activity. NEAT1 in MEG-01 cells was knocked down by siRNA transfection. The adhesion of MEG-01 and PLP to collagen-coated coverslips was observed under a fluorescence microscope. Flow cytometry was used to investigate cell apoptosis, cell cycle, the levels of D41/CD42b on MEG-01 cells and CD62P on PLPs. Quantitative real-time polymerase chain reaction was used to detect NEAT1 and IL-8 expression levels. Western blot was used to measure the protein levels of Bcl-2, Bax, cleaved caspase-3 and IL-8. RNA-binding protein immunoprecipitation was used to detect the interaction of NEAT1 and splicing factor proline/glutamine-rich (SFPQ). Results showed that NEAT1 knockdown decreased the adhesion ability of thrombin-stimulated MEG-01 and PLP. The expression of CD62P on PLPs and CD41/CD42b on MEG-01 cells were inhibited by NEAT1 knockdown. In addition, NEAT1 knockdown inhibited cell apoptosis with increased Bcl2/Bax ratio and decreased cleaved caspase-3, and reduced the percentage of cells in the G0/G1 phase. Meanwhile, NEAT1 knockdown inhibited the expression of IL-8. A strong interaction of NEAT1 and SFPQ, a transcriptional repressor of IL-8, was identified. NEAT1 knockdown reduced the interaction between SFPQ and NEAT1.The results suggest that lncRNA NEAT1 knockdown decreases MEG-01 differentiation, PLP activity and IL-8 level. The results also indicate that the regulation of NEAT1 on IL-8 may be realized via a direct interaction between NEAT1 and SFPQ.